Handbook of Recent Advances in Commodity and Financial Modeling Quantitative Methods in Banking, Finance, Insurance, Energy and Commodity Markets - Consigli, Giorgio; Stefani, Silvana; Zambruno, Giovanni (International Series in Operations Research & Management Science, 2018)
XIV, 320 p. 65 illus., 59 illus. in color.